New record and cytogenetic analysis of Psammolestes tertius Lent & Jurberg, 1965 (Hemiptera, Reduviidae, Triatominae) from Bahia State, Brazil - Oliveira, J. [UNESP]; Alevi, K. C. C. [UNESP]; Fonseca, E. O. L.; Souza, O. M. F.; Santos, C. G. S.; Azeredo-Oliveira, M. T. V. [UNESP]; Rosa, J. A. da [UNESP] (Funpec-editora, 2016)
This paper reports on the first occurrence of Psammolestes tertius in the Chapada Diamantina region, located in the city of Seabra, Bahia State, in northeastern Brazil. Following an active search, 24 P. tertius specimens were collected from Phacellodomus rufifrons (rufous-fronted thornbird) nests. The insects did not present any symptoms of infection by Trypanosoma cruzi. P. tertius males were cytogenetically analyzed, and the results were compared with those of other specimens from the Brazilian State of Ceara. Triatomines from both locations presented the same cytogenetic characteristics: 22 chromosomes, little variation in the size of the autosomes, Y chromosomes that were larger than the X chromosomes, a chromocenter formed only by the sex chromosomes during prophase, and autosomes lacking constitutive heterochromatin. However, it is important to note that this species shows intraspecific chromosomal variation. In light of the results obtained, it is recommended that more studies be performed to characterize P. tertius. These studies will be particularly helpful in understanding this species in ecological, biological, biogeographical, and phylogenetic terms.
Keywords: Triatominae subfamily; Chapada Diamantina; Chromosomal variation